UX Fundamentals for Non-UX Professionals User Experience Principles for Managers, Writers, Designers, and Developers - Stull, Edward (Apress, 2018)
Demystify UX and its rules, contradictions, and dilemmas. This book provides real-world examples of user experience concepts that empower teams to create compelling products and services, manage social media, interview UX candidates, and oversee product teams. From product decisions to performance reviews, your ability to participate in discussions about UX has become vital to your company's success as well as your own. However, UX concepts can seem complex. Many UX books are written by and for UX professionals. UX Fundamentals for Non-UX Professionals serves the needs of project managers, graphic designers, copyeditors, marketers, and others who wish to understand UX design and research. You will discover how UX has influenced history and continues to affect our daily lives. Entertaining real-world examples demonstrate what a massive, WWII-era tank teaches us about design, what a blue flower tells us about audiences, and what drunk marathoners show us about software. What You'll Learn: Know the fundamentals of UX through real-world examples Acquire the skills to participate intelligently in discussions about UX design and research Understand how UX impacts business, including product, pricing, placement, and promotion as well as security, speed, and privacy.